In Vitro Assessment of Developmental Neurotoxicity: Use of Microelectrode Arrays to Measure Functional Changes in Neuronal Network Ontogeny1 - Robinette, Brian L.; Harrill, Joshua A.; Mundy, William R.; Shafer, Timothy J. (Frontiers in Neuroengineering, 2011)
Because the Developmental Neurotoxicity Testing Guidelines require large numbers of animals and is expensive, development of in vitro approaches to screen chemicals for potential developmental neurotoxicity is a high priority. Many proposed approaches for screening are biochemical or morphological, and do not assess function of neuronal networks. In this study, microelectrode arrays (MEAs) were used to determine if chemical-induced changes in function could be detected by assessing the development of spontaneous network activity. MEAs record individual action potential spikes as well as groups of spikes (bursts) in neuronal networks, and activity can be assessed repeatedly over days in vitro (DIV). Primary cultures of rat cortical neurons were prepared on MEAs and spontaneous activity was assessed on DIV 2, 6, 9, 13, and 20 to determine the in vitro developmental profile of spontaneous spiking and bursting in cortical networks. In addition, 5 μM of the protein kinase C (PKC) inhibitor bisindolylmaleamide-1 (Bis-1) was added to MEAs (n= 9-18) on DIV 5 to determine if changes in spontaneous activity could be detected in response to inhibition of neurite outgrowth. A clear profile of in vitro activity development occurred in control MEAs, with the number of active channels increasing from 0 / MEA on DIV 2 to 37±5 / MEA by DIV 13; the rate of increase was most rapid between DIV 6 and 9, and activity declined by DIV 20. A similar pattern was observed for the number of bursting channels, as well as the total number of bursts. Bis-1 decreased the number of active channels / MEA and the number of bursting channels / MEA. Burst characteristics, such as burst duration and the number of spikes in a burst, were unchanged by Bis-1. These results demonstrate that MEAs can be used to assess the development of functional neuronal networks in vitro, as well as chemical-induced dysfunction.